Pneumonia caused by Sphingomonas paucimobilis infection after a dental intervention - Janković, Jelena; Gajić, Milija; Zečević, Andrej; Milivojević, Ivan; Buha, Ivana (The Journal of Infection in Developing Countries, 2023)
Introduction: Sphingomonas paucimobilis can be found in air, water systems, dialysis fluid, nebulizers and laboratory instruments in hospitals. Despite its low pathogenicity, it can cause severe infections. Case report: A 54-year-old man presented with fever, cough and pain in the right hemithorax. The laboratory results showed elevated inflammatory parameters. Chest radiography showed right upper lobe pneumonia. Empiric antibiotic therapy (cephalosporin) was prescribed. On control examination chest radiography showed incomplete regression. Chest computer tomography (CT) finding was bronchopneumonia in the right upper lobe. Bacteriological examination of fiberaspirate revealed Sphingomonas paucimobils. Trimethoprim-sulfamethoxazole was prescribed based on the antibiogram. After two weeks the control laboratory analysis was normal. The patient was fully recovered. Conclusions: Our patient had no comorbidities or malignancies, and no hospitalization in the recent past. He had a dental intervention 5 days prior to the onset of symptoms. We propose that it was an infection after the dental intervention.